Minimal compact operators, subdifferential of the maximum eigenvalue and semi-definite programming - Bottazzi, Tamara Paula (2025)
Fil: Bottazzi, Tamara Paula. Universidad Nacional de Río Negro. Centro Interdisciplinario de Telecomunicaciones, Electrónica, Computación y Ciencia Aplicada. Río Negro, Argentina